Pendidikan Berwawasan EkologI Realisasi Nilai-Nilai Ekologis dalam Kurikulum Pendidikan Agama Islam - Jatmiko, Agus (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
This research aims to express the realization of ecological values in Islamic Education Curriculum  in  Elementary  and  High  School.  The  problem  which  is  looked  for  answer  is, “How is the realization of ecological values in Islamic Education Curriculum in Elementary and High School?” This is qualitative research and data sources cover the books of Islamic Education Curriculum, its textbooks, and some books related to ecology. The data collected by  bibliography  study  (library  research),  and  later  examined  with  the  content  analysis technique. Its result indicates that the ecological values in Islamic Education Curriculum in the  school  as  whole  are  not  realized  explicitly,  thought  there  are  two  (0,  42%)  themes  of environment,  but  its  proportion  is  not  adequate.  Implicitly  there  are  ten  (2,11%)  themes which can be developed in order to internalize ecology values.